AB0394 Early Effect of Tofacitinib on Osteoclast Regulator in Rheumatoid Arthritis. (15th July 2016) - Kitano, M.; Kitano, S.; Sekiguchi, M.; Azuma, N.; Hashimoto, N.; Tsunoda, S.; Matsui, K.; Sano, H.
Abstract : Background: The selective Janus kinase (JAK) inhibitor tofacitinib has demonstrated excellent efficacy for rheumatoid arthritis (RA). These results suggest the possibility that tofacitinib improves osteoclastic bone destruction of RA. However, the detailed mechanism of tofacitinib for osteoclastogenesis in RA is pooly understood. In this study, we investigated the effect of tofacitinib on serum biomarkers related to osteoclast regulation such as soluble receptor activator of NF-kappa B ligand (sRANKL) and osteoprotegerin (OPG) in patients with RA. Objectives: To clarify the effect of tofacitinib on osteoclast regulator in RA. Methods: Fourteen patients with active RA who inadequate response to disease-modifying antirheumatic drugs (DMARDs) (mean age: 54.6 years, mean disease duration: 4.1 years, mean simplified disease activity index: 26.9, ACPA positive: 86%, oral steroid use: 29%, mean oral steroid dose: 10mg/day, MTX use: 93%, mean MTX dose:10.9mg/week, biologic DMARDs naïve: 57%) were started on treatment with tofacitinib 5mg twice daily (BID). Disease activity was assessed using the 28-joint count disease activity score-C-reactive protein sedimentation rate (DAS28-CRP) and simplified disease activity index (SDAI). Next, circulating levels of sRANKL and OPG were examined by enzyme-linked immunosorbent assay (ELISA) (sRANKL: human RANKL ELISA kit, Biomedica, OPG: human osteoprotegerin ELISA kit, Biomedica respectively) at the baseline, week 2, 4 and 12. Results: After treatment of tofacitinib, SDAI score among all fourteen patients decreased significantly from 26.9±12.4 (mean±SD) at the baseline to 14.7±9.9 at week 4 ( p <0.0001), to 8.3±6.1 at week 12 ( p <0.0001). Baseline levels of sRANKL were significantly correlated with the levels of CRP (Spearman r 2 =0.488, P=0.0054). Average of sRANKL levels decreased immediately from 0.15±0.11 pmol/L at the baseline to 0.09±0.05 pmol/L at week 2 ( p =0.0097), to 0.11±0.10 pmol/L at week 4 ( p =0.0311), to 0.08±0.05 pmol/L at week 12 ( p =0.0014). On the other hand, statistically significant changes in OPG levels were not observed during 12 weeks. Consequently, average of sRANKL/OPG ratio decreased significantly from 4.81±4.82 at the baseline to 2.62±1.84 at week 2 ( p =0.0186), to 3.11±2.81 at week 4 ( p =0.0191), to 2.11±1.72 at week 12 ( p =0.0052). Interestingly, decreasing effects of sRANKL levels or sRANKL/OPG ratio were greater in patient with high sRANKL level at the baseline. Conclusions: Here, we show for the first time that tofacitinib has improved inflammatory bone destruction immediately through the regulation of sRANKL levels and sRANKL/OPG balance in RA. This mechanism might be a control of RANKL induction via JAK pathway inhibition in activated CD4+ T cells and synovial fibroblasts Disclosure of Interest: None declared